Analysis And Simulation Of Pedestrian Walking Characteristic At Kuala Lumpur City Centre Underground Train Station - Lee, Chin Jie (Universiti Sains Malaysia, 2017)
The ridership of rail-transit system in Kuala Lumpur is increasing from year to year and the existing stations are getting more and more crowded as well. With the increasing space demand of the station, the ability of a station to handle such huge volume of pedestrians may be questioned. Study of the pedestrian walking characteristic in a train station may not only helps to reveal the current pedestrian traffic but may also help in future station design. These are achievable because it provides information for the designer to design an area that suit with current local pedestrian walking characteristic. In this study, data were collected through a closed-circuit television's footage provided by Prasarana Berhad Malaysia. This video footage had recorded the pedestrian walking activities in a concourse area inside the Kuala Lumpur City Centre underground light rail train station on 29 January 2015. The extracted data were analysed to determine the pedestrian walking speed and proportion of pedestrian in each path and direction. In term of walking speed, the analysed results showed the pedestrian walked faster toward corridor than walked toward shopping complex. The analysed results also showed that pedestrian tends to in the middle of the concourse area and the pedestrian also tends to walk on the left side of their path, which might probably be influenced by the Malaysian driving style. These finding, included the finding that explained in this study soon are useful to understand the pedestrian walking behaviour in a confined area inside a train station. These findings also can help for future pedestrian walking behaviour study and provide important data for future facilities design.